ANALYZING THE SILVER COINS FROM POTAISSA LEGIONARY FORT VS. ANCIENT TOWN - Razvan Bogdan Gaspar (Journal of Ancient History and Archaeology, 2015)
This paper is centered on the study of Roman silver coins from the archaeological site of Potaissa using as its main source M. Pîslaru’s book “The Roman coins from Potaissa: legionary fortress and ancient town”. The book focuses on the presentation of analysis results of monetary finds coming from Potaissa area while the article presents a different approach to the subject, by integrating part of the results in graphs that show a close-up perspective for the monetary evidence in chronological periods. How this task was accomplished is explained bellow, in two chapters, one dedicated for the study of the two areas from Potaissa, legionary fortress and civilian town, and another dedicated for the study of private coin collections from all of Potaissa.